(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Eichhornia crassipesis one of the most invasive and troublesome aquatic weed and causes serious ecological and financial harm to the aquatic ecosystem. Survey of water body, Taran Taaran taal of Datia (M.P) were conducted with the objective to isolate and evaluate the pathogenicity of native strains of fungal pathogens as biocontrol agent of Eichhornia crassipes. The fungal pathogensAspergillus ochraceus, Aspergillus niger, Fusarium oxysporum, Penicillium chrysogenum, Mucor irregularis, Mucor hiemalis and Rhizopus stolonifera were isolated and identified. After the pathogenicity test it has been found that Aspergillus nigerand Mucor irregularis causes disease symptoms resulting in the death of inoculated Eichhornia crassipesplants in about 18 days.